2022
DOI: 10.3390/su14094959
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Students Choose Buses over Private Motorcycles and Motorcycle-Based Ride-Sourcing? A Hybrid Choice Approach

Abstract: Improving public transport (PT) services is critical to maintaining resilient and sustainable transportation. While the investment in PT (i.e., buses) has not been able to shift private vehicle users, especially motorcyclists, to buses, the emergence of motorcycle-based ride-sourcing (MBRS) has become a popular travel mode that threatens the existing bus demand. Due to this, this study aimed to investigate the factors affecting the choice of buses over private motorcycles and MBRS among high school and univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 76 publications
0
1
0
1
Order By: Relevance
“…The five attributes to describe the services available in each mode included travel time, waiting time, travel cost, access time, and payment method, which were presented in the SP questionnaire to respondents. These attributes were drawn from prior studies that found they were the most popular in describing each mode choice for an Indonesian context, for example travel time and travel cost [63][64][65][66][67]. Some consider waiting time [63,64,66,67] for public transport, and some also consider access egress [64].…”
Section: Data and Survey Implementationmentioning
confidence: 99%
“…The five attributes to describe the services available in each mode included travel time, waiting time, travel cost, access time, and payment method, which were presented in the SP questionnaire to respondents. These attributes were drawn from prior studies that found they were the most popular in describing each mode choice for an Indonesian context, for example travel time and travel cost [63][64][65][66][67]. Some consider waiting time [63,64,66,67] for public transport, and some also consider access egress [64].…”
Section: Data and Survey Implementationmentioning
confidence: 99%
“…Hal ini juga berkaitan dengan adanya ancaman angkutan online yang masuk ke Yogyakarta pada akhir tahun 2015 (Wibowo, 2015). Irawan (2020) dalam Risdiyanto et al (2022) menyatakan bahwa meskipun jumlah penumpang pelajar pada Bus Trans Jogja tinggi, namun juga terancam keberadaan angkutan online, khususnya ojek online (Risdiyanto et al, 2022).…”
Section: Sebagaimanaunclassified